Podatkovne strukture pri simulaciji ogrevnih peči - Jaklič, Anton (Materiali in tehnologije, 2001)
The simulation of reheating furnaces is associated with an enormous amount of data which have to be processed in real time. Dealing mostly by recursive calculations it is preferable for the data to be saved in the computer's RAM. This allows faster manipulation of the data. The data structure determines the form of the data storing in the RAM. The appropriate data structure allows clearer programming; faster data access; and makes code more efficient and simplifies deleting and adding the data in the structure. In this contribution the chosen data structure for a walking-beam furnace and for a pusher-type furnace is presented. It is a pointer-based data structure, which can be dynamically adapted to the situation in the furnace.
Keywords: koračna peč; potisna peč; simulacije; podatkovne strukture